Laparoscopic Left Pancreatectomy: Does Exist a Learning Curve? - Ricci, Claudio; Buscemi, Salvatore; D’Ambra, Marielda; Taffurelli, Giovanni; Pacilio, Carlo Alberto; Peri, Eugenia; Pezzilli, Raffaele; Marrano, Nicola; Casadei, Riccardo; Minni, Francesco (JOP. Journal of the Pancreas, 2012)
Context Surgeons are performing laparoscopic left pancreatectomy (LLP) with increasing frequency. To our knowledge do not exist studies which defines learning curve (LC). Objectives To define a number of procedures needed to achieve LC in LLP. Methods From January 2008 to June 2012 data regarding 25 patients, undergoing LLP for pancreatic lesions, were collected in a prospective database. All procedures were performed by a single high volume surgeon in advanced laparoscopic and open pancreatic surgery. Decrease of the operative time (OT) was used as parameter to establish the achievement of LC. A preliminary multivariate analysis was carried out to establish which factors influenced OT. Correlation between OT and cumulative sum of procedure (CUSUM) was evaluated to calculate the LC cut-off. Finally multivariate analysis was repeated including LC cut-off. ANOVA test was used to estimate correlation and to calculate multivariate model. Results There were 18 (72%) females and 7 (28%) males with mean age of 55±16 years and mean BMI of 27±5 kg/m2. Patients were more frequently ASA II (64%). Thirteen patients (52%) presented one or more co-morbidity and had a previous surgical abdominal procedure. Splenectomy was carried out in 18 (72% ) cases. An extended resection was conducted in 5 cases (20%). Mean operative time was 219±52 min. Rate of conversion was 16%. Pathological examination showed only in 11 (44%) cases a malignant disease and none ductal adenocarcinoma. Preliminary multivariate analysis showed that splenectomy significantly decreased OT while size of lesion increased OT (P=0.033 and P=0.041, respectively). A significant inverse correlation was found between OT and CUSUM (P=0.050) and the LC cut-off was 14 procedures. Final analysis including LC cut-off showed that the achievement of LC cut-off reduced significantly OT (P=0.047). Instead BMI and extended resection independently increased OT (P=0.030 and P=0.022, respectively) Conclusion In our experience the number of procedure needed to achieve LC was 14 LLP. BMI and extended resection influenced OT even after the achievement of LC.